Women's Contexts and Circumstances of Posttraumatic Growth After Sexual Victimization: A Systematic Review - Guggisberg, Marika; Bottino, Simone; Doran, Christopher M. (Frontiers in Psychology, 2021)
Sexual violence is a concerning public health and criminal justice problem. Even though extensive literature has linked sexual victimization to a multitude of mental and physical problems, some victim/survivors recover and are able to lead lives without notable negative impacts. Little is known about women who experienced posttraumatic growth following sexual victimization. This review brings together knowledge accumulated in the academic literature in the past decade. It was informed by the PRISMA-P guidelines. Databases were searched using a combination of keywords to locate original peer-reviewed research articles published between January 2010 and October 2020 focusing on posttraumatic growth following sexual victimization. The initial search identified 6187 articles with 265 articles being read in full, identifying 41 articles that were included in the analysis. The results suggest that recovery from sexual victimization is possible with the healing process being idiosyncratic. Victim/survivors employed various strategies resulting in higher degrees of functioning, which were termed growth. Following a synthesis of themes that emerged from the thematic analysis, a higher order abstraction, using creative insight through reflexivity, discussions among the research team and consistent interpretation and re-interpretation of the identified themes as a second stage analysis, resulted in the identification of two superordinate topics ‘relationship to self’ and ‘relationship to others’. Findings indicated that, leading to women engaged in deliberate introspection to connect with themselves and utilized altruistic actions and activism in an attempt to prevent further sexual victimization. H Helping victim/survivors deal with the sexual violence facilitated growth as a collective. We concluded that helping others may be a therapeutic vehicle for PTG. Given research in this area remains in its infancy, further investigation is urgently needed.